Ultrasound-enhanced biosynthesis of uniform ZnO nanorice using Swietenia macrophylla seed extract and its in vitro anticancer activity - Low Darren Yi Sern (De Gruyter, 2021)
In this study, ultrasonically driven biosynthesis of zinc oxide nanoparticles (ZnO NPs) using Swietenia macrophylla seed ethyl acetate fraction (SMEAF) has been reported. X-ray powder diffraction (XRD) and Fourier-transform infrared spectroscopy (FTIR) analyses confirmed the presence of a pure hexagonal wurtzite structure of ZnO. Field emission scanning electron microscope images revealed the formation of uniquely identifiable uniform rice-shaped biologically synthesized ZnOSMEAF particles. The particle sizes of the biosynthesized NPs ranged from 262 to 311 nm. The underlying mechanisms for the biosynthesis of ZnOSMEAF under ultrasound have been proposed based on FTIR and XRD results. The anticancer activity of the as-prepared ZnOSMEAF was investigated against HCT-116 human colon cancer cell lines via methyl thiazolyl tetrazolium assay. ZnOSMEAF exhibited significant anticancer activity against colon cancer cells with higher potency than ZnO particles prepared using the chemical method and SMEAF alone. Exposure of HCT-116 colon cancer cells to ZnOSMEAF promoted a remarkable reduction in cell viability in all the tested concentrations. This study suggests that green sonochemically induced ZnO NPs using medicinal plant extract could be a potential anticancer agent for biomedical applications.